Control interno del comercial peña del cantón Ventanas, provincia de Los Ríos, año 2013 - Álvarez Bustamante, Lucciola Noemi (2013)
Comercial Peña is incorporated, and has about 15 years’s experience in agricultural trade , is located in the canton Windows, in the province of Los Rios, currently , the company has weaknesses in the internal control system that applies these problems are reflected in an inadequate level of efficiency activities , because there is no manual functions and procedures are not opportunely supervised the activities that the human talent , physical inventory taking of products is performed in any time , is counting on the good faith of human talent working in the company , now this could represent a significant loss of resources to the company . These difficulties detected when evaluating the internal control system of the company was run , in this evaluation the procedures were applied , and was known in a general way the company were interviewed administrative, accounting and operational staff ; were surveyed with questions relevant to human talent , a sample of providers and a sample of customers , we proceeded to evaluate the system of internal control based on the COSO method , and once completed independent auditor 's report was issued and the respective recommendations. The project contains the introduction, rationale, objectives, assumptions, theoretical framework, research results detailing the evaluation process with their support documents current internal control, and ending with the Report of Independent Auditor.